Analisis Pengaruh Inflasi, Nilai Tukar Rupiah, dan BI-Rate terhadap Harga Indeks Saham Syariah Indonesia - Tripuspitorini, Fifi Afiyanti (Jurnal Maps (Manajemen Perbankan Syariah), 2021)
Islamic investment is experiencing an upward trend from year to year. Many investors are starting to look at Islamic stocks. One of the Islamic stocks in Indonesia is the Indonesian Sharia Stock Index (ISSI). Investors must have many careful considerations to invest. One of the factors that may influence stock prices is macroeconomic factors. This study aims to determine how macroeconomic variables in the form of inflation, the rupiah exchange rate against the dollar, and Bank Indonesia interest rates can affect the ISSI stock price. This study uses a quantitative data approach. The data is obtained from the Sharia Stock Index (ISSI) in the monthly period January 2016 to December 2018.Meanwhile, data analysis used Partial Least Square (PLS) with the help of WarpPLS. The results showed that inflation and the rupiah exchange rate had no effect on the ISSI stock price. while the BI rate has a significant negative effect on the ISSI stock price.